Gender differences in the nutritional pattern of the adult population of the Russian Federation. The results of ESSE-RF epidemiological study - N. S. Karamnova; S. A. Shalnova; V. I. Tarasov; A. D. Deev; Yu. A. Balanova; A. E. Imaeva; G. A. Muromtseva; A. V. Kapustina; S. E. Evstifeeva; O. M. Drapkina (Российский кардиологический журнал)
Many nutritional studies have noted that men and women form their diets from various food sources, preferring different dishes.Aim. To study the sex differences in the nutritional pattern of the adult population of the Russian Federation according to the epidemiological study.Material and methods. The analysis was performed on representative data from male and female population aged 25-64 years (22,258 people, of whom 8,519 men and 13,698 women) from 13 regions of the Russian Federation. The response was about 80%. The nutritional pattern was estimated by the frequency of food consumption with individual quantitative assessment.Results. The most pronounced differences in men and women diets were observed in the consumption of fresh vegetables and fruits, dairy products, meat, and confectionery products. Women more often than men include in their diet (odds ratio, 95% CI): raw vegetables and fruits 1,45 [1,33-1,59], sweets and pastries 1,22 [1,33-1,59] , dairy products 1,57 [1,39-1,76], in particular, cottage cheese 1,69 [1,60-1,79], milk 1,46 [1,36-1,56] and cheese 1,31 [1,23-1,40]. The number of daily consumption of fruits and vegetables is more significant in the diet of women — 207,6 g/day versus 165,8 g/day for men, p<0,0001. Women are less likely to consume men; red meat 0,43 [0,39-0,46], sausage products — 0,63 [0,59-0,67], cereals and pasta — 0,79 [0,74-0,86], pickles and marinades — 0,79 [0,75-084], fish and seafood — 0,79 [074-0,86]. There were no gender differences in the level of consumption of leguminous products. Among men, the habit of adding more salt to food is more common — 47,0% against 34,7%, p<0,0001.Conclusion. Women more often than men include in the diet vegetables and fruits, dairy products and confectionery, less often — products of animal origin (meat, sausages, fish and seafood).Participants of the ESSE-RF study and co-authors of the article: Moscow: Zhernakova Yu. V., BoytsovS. A., Saint-Petersburg: Rotar O. P., Vladivostok: Kulakova N. V., Nevzorova V. A., Vladikavkaz: Astakhova Z. T., Vologda: Shabunova A.A., Volgograd: Nedogoda S.V., Voronezh: Chernykh T. M., Ivanovo: Belova O. A., Kemerovo: Artamonova G. V., Indukayeva E. V., Krasnoyarsk: Grinshtein Yu. I., Petrova M. M., Orenburg: Libis R. A., Samara: Duplyakov D. V., Tomsk: Trubacheva I. A., Kaveshnikov V. S., Serebryakova V. N., Tyumen: Efanov A. Yu., Medvedeva I. V., Shalaev S.V.